Auto Body Repair Technology \ - Duffy, James E. (Australia : Cengage Learning, 2016)
Features material reflecting the automotive technology and industry best practices. In addition to incorporating NATEF Collision Repair and Refinish Program Standards and Task Lists, this book provides information on working with hybrid and electric vehicles, using environmentally friendly water-based paints, and other methods and materials.
Introduction -- Estimating -- Minor repairs -- Major body/frame repairs -- Mechanical and electrical repairs -- Refinishing -- Collision repair professionalism.
Includes index.
hard cover
Keywords: Automobiles -- Bodies -- Maintenance and repair; Automobiles -- Collision damage